Performance of generalized frequency division multiplexing over gamma gamma free space optical link - Ahmed, Muhammad Sameer; Gucluoglu, Tansal (ELSEVIER, 2020)
Generalized frequency division multiplexing (GFDM) with the free space optical channel can be a desirable option for free space optical communication systems as it has numerous benefits such as high spectral efficiency, flexibility, low out of band radiation and low peak-to-average power ratio. In this paper, the closed form expressions of symbol error and outage probabilities with and without pointing errors are derived for GFDM over gamma-gamma channel model. The theoretical results are verified with the Monte-Carlo simulations. Moreover, the impact of turbulence levels and comparison with orthogonal frequency division multiplexing are also explored.
Keywords: Free space optics; Generalized frequency division multiplexing; Orthogonal frequency division multiplexing; Gamma gamma distribution; Atmospheric turbulences; FSO LINKS; GFDM; OFDM; COMMUNICATION; RECEIVER; BER; Optics